CAMPUR KODE BAHASA IBU TERHADAP PERCAKAPAN BAHASA ARAB PONDOK PESANTREN DARUL IMAN - Sani, Nurhikmah; Nurazim, Okitra Asri; Rahmatan, Madah; Alvio JH, Depaty; Pratama, Ridho (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
In Pondok pesantren Darul Iman, students are required to communicate using the Arabic language, so researchers are interested in examining whether in Pondok pesantren Darul Iman, there is a mix of Arabic and mother tongue code which is the language they learned from birth, as well as to determine the factors and forms of mixed language code in conversation at pesantren Darul Iman, the method used in this study is a qualitative descriptive method. The results of this study showed that there is a mix of codes that occurs in the conversation of Islamic boarding school students. Darul Iman is divided into three formations, namely: (1) mix the code of Indonesian to Arabic, (2) mix the code of regional languages to Arabic. This study found the type of outer code mixing in the form of insertion and congruent lexicalization. The factors that cause language mixing in the conversation of students at Pondok pesantren Darul Iman are: (1) limitations in vocabulary, (2) background of speakers, (3) mixing codes occurs due to the situation, (4) speech partners with the same background, (5) speakers do not find the right word equivalent, (6) clarification and refinement of requests, (7) the habit of interacting using regional languages.